Tendon transfer for median nerve palsy - K. Sridhar (Indian Journal of Plastic Surgery)
The article describes the approach practiced by the author from 1995. Mainly Hansen's patients and lower forearm injuries formed the bulk of these. In Opponen's transfer ECU was used only when others were not available as the wrist developed a tendency to radial deviation even when FCU was acting. PL with palmar aponeurosis as extension was used again in limited cases. The main stay was FDS and EIP. The Guyan's canal and lower end of ulna were the common pulleys. APB and EPL two slip inserts yielded good results. The approach describes the procedure under three distinct headings of choosing motor, Pulley and insert. Varying combinations of these can be used as per requirement.